Multiculturalism and Gender Values in Arabic Language Learning in Islamic University - Mubarok, Mochamad Gilang Ardela Mubarok; Ruswandi, Uus; Erihadiana, Muhamad; al-Bahri, Adel Ahmed Ali; Mohammed al-Azzani, Gamil Taher Ahmed (Postgraduate of IAIN Metro Lampung Indonesia, 2024)
This study aims to explore the integration of multiculturalism and gender values in the Arabic language learning process at Islamic universities. Using qualitative research methods, the study analyzes learning content through observations and interviews. The findings reveal that multicultural and gender values are embedded in the textbooks used and are also reflected in the approaches, strategies, methods, and techniques employed by lecturers. These values are consistently emphasized throughout the Arabic language learning process. The results of this study provide valuable insights for further research on Arabic language education, particularly in the context of multiculturalism and gender equality. Unlike previous research, this study simultaneously addresses these two critical issues in education, highlighting that multicultural education cannot be fully effective without also considering gender equality as an integral part of the learning process.